Effects of plant growth regulators (6-benzylaminopurine and kinetin) on shoot production of Cavendish banana - Saad, Nur Atiqah (2018)
Cavendish Banana is known as one of the most important food crops for the society throughout the world as it provides various functions and needs especially for the food security. Micro propagation is the best alternative way to produce multiple number of planting materials. The main objective of this study was to investigate the effects of using different cytokinin (6-benzylaminopurine and Kinetin) as plant growth regulators with different concentrations to induce shoot productions on sucker of Cavendish Banana. The explants were cultured on Murashige and Skoog (MS) medium supplemented with five levels of cytokinins concentration (1.0, 2.0, 3.0, 4.0 and 5.0mg/L) and 0.0mg/L as a control; each of it was cultured with five replicates. After 30 days of observations, the highest number of shoots and the length of the longest shoots were observed in MS media with 1.0mg/L concentration of BAP which was higher compared to Kinetin.